A Comparative Analysis of Open versus Endovascular Techniques for Management of Non-Aortic Cervicothoracic Arterial Injuries. Issue 10 (October 2017) - Gray, Kelsey; Beckord, Brian; Moazzez, Ashkan; Plurad, David; Bowens, Nina; Kim, Dennis
The objective of this study is to describe the contemporary management of proximal upper extremity and neck arterial injuries by comparing open and endovascular repair at a single institution. This is a retrospective study of 22 patients that sustained subclavian, axillary, and carotid artery injuries from 2011 to 2016 that were managed with open or endovascular repair. There were nine subclavian, eight axillary, and five carotid artery injuries of which 10 (45.5%) underwent endovascular repair and 12 (54.5%) underwent open repair. There was no statistically significant difference between the groups including injury severity score or preoperative hypotension. There were no deaths in the endovascular group, and three (25.0%) deaths in the open group. All patients in the endovascular group were discharged home. In the open group, seven (58.3%) patients had at least one inpatient complication with a mean of 1.1 (standard deviation 1.4) complications per patient. In the endovascular group, there were three (30.0%) patients with inpatient complications and a mean of 0.4 (standard deviation 0.7) complications per patient (P = 0.18). Endovascular management of nonaortic cervicothoracic arterial injuries was successfully performed in hypotensive patients and patients with other life threatening traumatic injuries. Further studies are warranted to look at long-term patency of these repairs and to help develop a protocol to guide decision-making in the management of cervicothoracic injuries.